2009
DOI: 10.3109/02841860903287197
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase (MMP)-7 in salivary gland cancer

Abstract: MMP-7 is associated with the prognosis of patients with acinic cell and mucoepidermoid carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…This is supported by similar results from other tumor types. Luukaa and coworkers showed that high expression of MMP-7 in acinic cell carcinomas and mucoepidermoid carcinomas of the salivary glands, was associated with a better overall survival [19]. In consistency, Ito et al found in papillary thyroid carcinoma that low tumor cell MMP-7 and MMP-11 expression was associated with aggressive tumor characteristics indicative of poor prognosis [20].…”
Section: Discussionmentioning
confidence: 92%
“…This is supported by similar results from other tumor types. Luukaa and coworkers showed that high expression of MMP-7 in acinic cell carcinomas and mucoepidermoid carcinomas of the salivary glands, was associated with a better overall survival [19]. In consistency, Ito et al found in papillary thyroid carcinoma that low tumor cell MMP-7 and MMP-11 expression was associated with aggressive tumor characteristics indicative of poor prognosis [20].…”
Section: Discussionmentioning
confidence: 92%
“…MMP7 expression was associated with favorable prognosis of malignant neoplasms of ovary and salivary gland [11,20], while in cholangiocarcinoma and esophageal squamous cell carcinoma, CD133 negativity was related to advanced tumor stage and poor prognosis [4,16]. Negative Oct3/4 expression was correlated with invasion depth, lymph node metastasis, and lymphatic invasion of gastric cancer [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, the limit of detection (LOD) achieved by this assay was 5 nM, approximately equivalent to the critical level of MMP-7 related to salivary gland cancer. 12 Moreover, performance of this MMP-7 assay in clinical sample matrices was not demonstrated.…”
mentioning
confidence: 99%